Digging Deeper: Understanding the Illegal Trade and Local Use of Pangolins in Palawan Province, Philippines - Archer, Lucy J.; Turvey, Samuel T.; Apale, Charity M.; Corona, Darlyn B.; Amada, Ronald L.; Papworth, Sarah K. (Frontiers in Conservation Science, 2021)
The illegal wildlife trade represents an urgent conservation challenge, but measuring, understanding, and designing interventions to address it is a complex task. As some of the world’s most illegally trafficked wild mammals, pangolins are regularly observed in the illegal wildlife trade, but little is known of the intricacies of the trade at local levels, particularly for lesser-known species such as the Philippine pangolin (Manis culionensis). This research represents the first range-wide study to concurrently document local use and trade of the Philippine pangolin across Palawan Province, Philippines, and provides new information on trade actors, dynamics, and the conditions that help to facilitate this industry. The study was carried out across 18 Palawan municipalities, covering all mainland municipalities, Araceli Island, and the Calamianes Island group. A mixed methods approach was used, combining 1,277 bean count surveys to investigate consumption and hunting levels, alongside 59 in-depth key informant interviews to better understand trade logistics and dynamics. Our results suggest that local use of the species is geographically widespread, but trade hubs were most frequently reported from northern municipalities. Several enabling conditions help facilitate trade across the province, and our data suggest the species may be contributing to the international pangolin trade at levels considerably higher than seizure records indicate.